PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN PERILAKU ETIS TERHADAP KINERJA AUDITOR PEMERINTAH (Studi Empiris pada BPK-RI dan BPKP Perwakilan Provinsi Riau) - Taufik, Taufeni; Hasan, Mudrika Alamsyah; ', Apriyanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study was conducted using a survey method. With the aim to find empirical evidence of the influence of emotional intelligence, spiritual intelligence and ethical behavior on the performance of government auditors. The population in the study were all auditors working on BPK - RI and BPKP Representative Riau Province . Samples taken amoundted to 35 auditors of BPK-RI and 67 auditors of BPKP Representative of the Riau Province . The type of data used is primary data by using questionnaire method of data collection . The method of data analysis used in this study is multiple regression ( multiple regression ) with the help of software SPSS version 17:00 The results show that emotional intelligence, influence the auditor's performance with value t count 4,997, t-table 0.194 significant 0.000. Spiritual Intelligence affect the performance of thauditor with a value of 3,141 t-test, t-table 0.194 significant 0.003 and ethical behavior significantly affect the performance of the auditor with a value of 2,659 t-test, t-table 0.194 , significant 0.009. R-square value is equal to 0.565 which means that 56.5% of the independent variables in this study were able to influence the dependent variable, while the remaining 33.5% is explained by other variables not included in this study, such as: intellectual intelligence and job satisfaction.Keywords : Emotional Intelligence, Spiritual Intelligence, Ethical behavior, Performance Auditor